PENGEMBANGAN SOAL LATIHAN BENTUK PERMAINAN MODEL TIC TAC TOE BERBASIS KOMPUTER PADA MATERI POKOK STRUKTUR ATOM, BENTUK MOLEKUL DAN GAYA ANTAR MOLEKUL - Devin Hindarta, ; Sukarmin, (Jurnal Penelitian Pendidikan Matematika dan Sains, 2010)
It has been done the developing research of tic tac toe game as a facility of practicing students about atomic structure, molecular shape and inter-molecular forces subject matter. Research purposes to determine themedia feasibility based on the teacher validation. The assessment criteria  include the accuracy of formats, quality, and media as well as evaluating from students includes the precision criteria of formats, media quality and interest of students/benefits of the media. This research software development refers to learning model 4D (four-D model) according to Thiagarajan (1974), which is limited to three stages, namely stage of defining (Define), stage design (Design), stage of development (Development). The result from validation chemistry teacher and the limited try out  in class XI student SMAN I Wonoayu, Sidoarjo. Indicators of feasibility achievement of tic tac toe game media get responses of ≥ 61% o score kreterium from the teacher and student. The results showed that the media play tic tac toe on the subject matter atomic structure, molecular shape and inter-molecular forces are developed for students to class XI have been fit for use on student learning with teacher assessment results at 85.00% for the accuracy of media formats and 85, 00% quality of the media, while the assessment of students at 74.67% for the accuracy of media formats, 75.20% and 87.60% of media quality for the benefit / interest of students.